Aspects of the theory of Dionysius the Areopagite concerning the Divine Processions as generating principles of the cosmos - Terezēs, Chrēstos Ath. ca. 20./21. Jh. (Augustinianum, 2012)
In this study we attempt to present the argumentation through which Dionysius the Areopagite constructs his theory concerning the processions - powers - capacities of the supreme Principle, the One or the Good, in order to distinguish it from the multitude of produced beings. His main aim, in our opinion, is to avoid pantheism. With reference both to what the Areopagite has borrowed from the Neoplatonic philosophy, and to the distance he moves away from it, we approach views which have been formulated by other scholars, mainly by O. Semmelroth, E. Corsini and S. Gersh. Our purpose is to show that the processions consist in the projection of the One for the creation of the natural world and that, at the same time, they are not ontologically inferior to its hypostasis.